(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
The current research focuses on the development of hybrid composites utilising natural fibre reinforcement and fillers with polymer resin for engineering applications. Natural fibres and filler materials have received substantial interest because of their environmentally beneficial and sustainable properties. Using the hand lay-up method, five hybrid composite samples were fabricated by keeping the jute fibre and flax fibre weight % ratio at 5(wt.%): 15(wt.%) and altering the granite powder filler weight percentage (0, 5, 10, 15, and 20 wt.%) in epoxy resin. A universal testing machine was used to assess the hybrid composites’ tensile and flexural strengths, and an Izod impact tester was used to determine their impact strength. Mechanical tests demonstrated that the inclusion of granite powder filler improved the mechanical properties in the fibres up to 15 wt.%, but then decreased owing to filler agglomeration. The thermo-gravimetric analysis was used for evaluating the thermal response of the samples, or thermal stability of the hybrid composites and are thermally stable up to 420°C. Furthermore, Fourier Transform Infra-Red spectroscopy was used to trace the existence of chemical functional groups in the hybrid composite. Scanning Electron Microscopic examination was used to confirm the interfacial bonding and failure modes of tested hybrid composites. The results indicate that these hybrid composites can be used in various applications, such as structural panels for vehicles, automobiles, aerospace, and construction. Thus, combining otherwise-unused granite powder with jute and flax fibres yields methods for recycling waste and making eco-friendly composites.